AB0970 Treatment with 4jointz reduces knee pain over twelve weeks of treatment in patients with clinical knee osteoarthritis: A randomised controlled trial. (23rd January 2014) - Laslett, L.L.; Quinn, S.J.; Darian-Smith, E.; Kwok, M.; Fedorova, T.; March, L.; Jones, G.
Abstract : Background: Knee osteoarthritis (OA) is a leading cause of chronic disability. OA management involves symptom control, usually non-steroidal anti-inflammatory (NSAIDs) or analgesic medication in early OA, then joint replacement in late OA. The controversy surrounding use of the COX-2 inhibitor class of NSAIDs and heightened cardiovascular risk, 1-3 highlights the importance of finding safer treatment options to minimise adverse side effects. The use of natural agents may play a role in treatment of OA even if they are only moderately effective. Comfrey (Symphytum officinale) and tannic acid are excellent treatment candidates, as comfrey has anti-inflammatory and analgesic properties, and antioxidants (such as tannic acid) protect against the high levels of free radicals and reduced levels of antioxidants 4 observed within the joint fluid. 5 Both have been used separately to treat OA. 6-8 Objectives: To assess the efficacy of thrice daily topical 4jointz utilizing Acteev technology (a novel and patented combination of a standardized comfrey extract and a pharmaceutical grade tannic acid, 3.5 mg/day), or placebo on osteoarthritic knee pain, markers of inflammation and cartilage breakdown over twelve weeks in a twelve-week double-blind randomised controlled trial. Methods: Adults aged 50-80 years (n=133) with clinical knee OA according to the ACR criteria were randomised to receive either 4jointz or placebo in addition to existing medications. The primary outcome measure was the pain VAS at 12 weeks. Pain and function were measured using a visual analogue scale (VAS) and the Knee Injury and Osteoarthritis Outcome Score (KOOS) scale at baseline, 4, 8 and 12 weeks. Inflammation was measured using IL-6 and cartilage breakdown using CTX-2 at baseline and twelve weeks. Results: Pain scores had a greater reduction in the group who received 4jointz compared to the group who received placebo after twelve weeks using both the VAS (-9.9mm, p=0.034) and the KOOS pain scale (+5.7, p=0.047). Muscle strength improved after twelve weeks (2.9 kg, p=0.02). Changes in IL-6 and CTX-2 were not significant (-0.1, p=0.96; -5.8, p=0.62). Reduction in paracetamol daily dose (mg) in patients using paracetamol at baseline was clinically (but not statistically) significant by twelve weeks (-404 mg, p=0.35) Post hoc analyses suggested that treatment may be most effective in women (VAS -16.8mm, p=0.008) and those with milder radiographic osteoarthritis (VAS -16.1mm, p=0.009). Local rash was more common amongst participants receiving 4jointz (19% v 1.6%, IRR 13.2, p=0.013), but only 22% (n=3) of participants with rashes discontinued treatment. There were no changes in systemic blood results and no differences in adverse events between patients receiving 4jointz and placebo. Conclusions: Topical treatment using 4jointz reduces symptoms of osteoarthritis over twelve weeks of treatment. References: Bombardier C, et al. N Engl J Med 2000;343:1520-8. Bresalier RS, et al. N Engl J Med 2005;352:1092-102. Solomon SD, et al. N Engl J Med 2005;352:1071-80. Cho ML, et al. Immunol Lett 2009;124:102-10. Regan EA, et al. Osteoarthritis Cartilage 2008;16:515-21. Grube B, et al. Phytomedicine 2007;14:2-10. Koll R, et al. Fortschr Med Orig 2002;120:1-9. McAlindon TE, et al. Arthritis Rheum 1996;39:648-56. Disclosure of Interest: L. Laslett: None Declared, S. Quinn: None Declared, E. Darian-Smith: None Declared, M. Kwok: None Declared, T. Fedorova: None Declared, L. March: None Declared, G. Jones Grant/Research support from: Arthritis Relief Plus Pty Ltd